Strength of Reactive Powder Concrete Beam-Column Joints Reinforced with High-Strength (HRB600) Bars under Seismic Loading - Wang, D.H.; Ju, Y.Z.; Zheng, W.Z. (Проблемы прочности, 2017)
In order to study the seismic behavior of reactive powder concrete beam-column joints reinforced with high-strength bars, an experimental investigation was carried out. A total of 5 reinforced reactive powder concrete exterior joint specimens (including 2 specimens with HRB600 steel bars and 3 specimens with HRB400 steel bars) were cast and tested. The seismic behavior of 5 existing test specimens was studied, including failure mode, hysteretic behavior, deformation capacity, ductility, energy dissipation capacity, and strength and stiffness degradation. The results showed that failure modes of reactive powder concrete beam-column joints under reversed cyclic loading are mainly flexural failure of the beam adjacent to the joint core, shear failure of the joint core, or combined failure of the plastic hinge in the beam and shear in the joint core. The configuration of HRB600 bars in reactive powder concrete beam-column joints alleviates the destruction, reduces the degradation of strength and stiffness, lessens residual deformation, and enhances both deformation capacity and energy dissipation capacity. Stirrups in the joint core directly bear part of the shear forces and provide confinement to the reactive powder concrete. Therefore, the utilization of stirrups in joints can retard the development of diagonal cracks, slow the degradation of strength and stiffness, and enhance the bearing capacity and energy dissipation capacity of the joint.